MOTIVASI KERJA GURU DI SMP NEGERI SUB RAYON 2 MUNTILAN KABUPATEN MAGELANG (Suatu tinjauan aspek persepsi guru tentang supervisi kepala sekolah, profesionalisme guru, dan iklim sekolah) - Nugrahantini, Nanik Istantri (Jurnal VARIDIKA, 2013)
The aim of this research is to describe and explain teacher perception influence about headmaster supervision, work climate, and teacher professionalism towards teacher work motivation at SMP country for area 02 muntilan regency magelang. The sample is taken with random proportional technique sampling in error level 5% with Kretcie table as big as 117 from 175 teachers. Data collecting for all variable, use closed inquiry method based on test result has tried the instrument has been declared valid and reliable. The data analysis technique for interval characteristic data, used multiple regression analysis in 5% standard signification. classic assumption for this Multiple regression applications, are normality data distribution, linearity, nonmulticolinearity test, homoscedasticity test and otokorelation test, are BLUE. The result of this research show that connection causal deliver variable that canvassed to show level significations that certifiable in ts. 5%. as to this result is braced with contribution coefficient as big as 63,9% detailed for headmaster supervision factor as big as 19,7%, work climate as big as 20,6% and teacher professionalism 23,6%.